Analisis Sengketa Kewenangan Antara Pemerintah Pusat dan Pemerintah Daerah dalam Pelaksanaan Otonomi Daerah - Damiti, Alex; Firmansyah, Royzd; Latif, Anas; Moonti, Roy Marthen (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The central government is the highest level of government in a country that has the greatest power and authority. The central government is responsible for controlling the unitary state, making decisions and rules for the whole country, and exercising national supremacy over other governments. Local government is the administration of government affairs by the local government and the Regional People's Representative Council (DPRD). Local government is carried out based on the principles of autonomy and assistance with the principle of the widest possible autonomy. Regional autonomy is a concept in which the central government grants a number of authorities to local governments to regulate and manage their own government affairs in accordance with laws and regulations in the Indonesian context, regional autonomy is regulated in Law Number 23 of 2014 concerning Regional Government. The purpose of regional autonomy is to realize effective and efficient government and improve the welfare of the community.